Adsorption of Anionic and Cationic Dyes in Batik Wastewater Using Biomass Adsorbents: Literature Review - Shofi Kurniawati; Nurma Yunita Indriyanti (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2021)
This literature review aims to determine: 1. the content of chemical compounds in biomass waste, 2. the modification methods of biomass waste to be used as an adsorbent, 3. the suitable parameters for adsorbing anionic and cationic dyes. This literature review was conducted by Seven Steps Comprehensive Literature Review and reviewed 41 articles with the filtration processes. First, the search results using certain keywords in the Google Scholar database obtained 449 articles. Selection by year of publication (2016-2020), becomes 295 articles. Selection by duplicate and irrelevant articles, becomes 56 articles. Selection by publication type, becomes 47 articles. Lastly, full-text article screening becomes 41 articles. The results of this literature review show that: 1. Sources of biomass adsorbents include tea waste, peanut shells, cassava dregs, cassava peels, oil palm empty bunches, coffee grounds, corn cobs and coconut shavings. The content of chemical compounds in biomass waste include cellulose, hemicellulose and lignin. The highest content of cellulose was found in peanut shells at 63,5%; hemicellulose was in coffee grounds at 40,55%; and lignin was in wood shavings at 17-35%. The content of cellulose in the adsorbent source affects the adsorption ability of the adsorbent produced. 2. The modification methods of biomass adsorbent include carbonization, physical and chemical activation, and nanocomposites. The adsorption capacity of the adsorbents made by the carbonization-activation, chemical activation, and nanocomposite manufacturing method are 102,77 – 332,6 mg/g; 26,67 – 236,6 mg/g; and 12,42 mg/g, respectively. 3. Parameters that affect the adsorption of anionic and cationic dyes are pH, contact time, adsorbent mass, and initial concentration of the adsorbate solution. The optimum conditions for anionic dyes adsorption by biomass adsorbents occurred at pH 2-4, contact time 30 – 40 minutes, 0,1 – 0,2 g of adsorbent mass, and initial concentration 80 – 100 mg/L. While the optimum conditions for cationic dyes adsorption occurred at pH 5-9, contact time 60 – 90 minutes, 0,2 – 0,3 g of adsorbent mass, and initial concentration 100 – 120 mg/L.